DIGITALISASI SISTEM PEMBAYARAN BERBASIS QR CODE UNTUK MENDORONG TRANSAKSI NON-TUNAI DI PASAR TRADISIONAL DI KOTA YOGYAKARTA (Fakultas Ekonomi Universitas Islam Kadiri (UNISKA) Kediri, 2025)
Traditional markets as centers of grassroots economy are still dominated by cash transactions that limit efficiency and integration with the digital financial ecosystem. This research examines the implementation of QR code-based payment systems as a digitalization solution for transactions in traditional markets. The research methodology employs a qualitative approach through participatory observation and in-depth interviews with 25 vendors and 50 consumers across three traditional markets in Malang City. Results indicate that QR code technology adoption increased transaction volume by 27% and transaction time efficiency by up to 68% compared to conventional cash transactions. Major challenges include merchants' digital literacy, network infrastructure availability, and cash transaction habits. The implementation was successfully supported by intensive training and transaction incentives, demonstrating QR codes' significant potential as a catalyst for traditional market transformation toward an inclusive digital economic ecosystem.